2009
DOI: 10.1093/eurheartj/ehp180
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke and cardiometabolic risk in young children: results from a survey in south-west Germany

Abstract: Among children, ETS exposure was associated with a low-grade inflammatory response and altered markers of lipid metabolism, which may initiate atherosclerosis in early life. However, longitudinal studies are necessary to determine the potential causal relevance of these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
2
19
2
3
Order By: Relevance
“…Hypertriglyceridemia can still be indicative of fatty liver development that is related to smoking (Chiang et al 2009, Mallat & Lotersztajn 2010. Tobacco smoke is related to decreased Apo AI and other cardiometabolic alterations in children exposed to ETS (Nagel et al 2009); however, in our model, S pups had higher HDL-C levels suggesting an adaptive defense mechanism against tobacco smoke effects. Perhaps, nicotine is responsible for higher serum HDL-C because recently we evidenced this effect in suckling pups whose mothers were treated with nicotine during lactation .…”
Section: Discussioncontrasting
confidence: 53%
“…Hypertriglyceridemia can still be indicative of fatty liver development that is related to smoking (Chiang et al 2009, Mallat & Lotersztajn 2010. Tobacco smoke is related to decreased Apo AI and other cardiometabolic alterations in children exposed to ETS (Nagel et al 2009); however, in our model, S pups had higher HDL-C levels suggesting an adaptive defense mechanism against tobacco smoke effects. Perhaps, nicotine is responsible for higher serum HDL-C because recently we evidenced this effect in suckling pups whose mothers were treated with nicotine during lactation .…”
Section: Discussioncontrasting
confidence: 53%
“…36 Additionally, in a meta-analysis relevant to the current study, PSE has been linked with increased risk of type 2 diabetes in adults, though mechanisms to explain this remain unclear. 37 Mechanisms linking PSE with adverse effects on cognition include hypoxia or increased carbon monoxide exposure from PSE.…”
Section: Discussionmentioning
confidence: 77%
“…We evidenced that neonatal tobacco smoke programs for higher triglycerides, VLDL-C, and HDL-C in adult life. Initially, higher HDL-C seems to be contradictory as tobacco SE is associated with lower serum HDL-C in children (Nagel et al 2009, Hirata et al 2010. However, increased HDL-C was found in adult female rats who were exposed to tobacco smoke during gestation without change in total antioxidant capacity, suggesting that higher HDL-C is non-functional (Ng et al 2009).…”
Section: Adulthood Alterationsmentioning
confidence: 99%
“…The WHO (2009) showed that 40% of children are submitted to cigarette components by environmental tobacco smoke, when at least one of their parents is a smoker. Children exposed to environmental tobacco present higher serum leptin, C-reactive protein, fibrinogen, and interleukin-6 levels (Nagel et al 2009), which suggest more susceptibility to cardiovascular disease. As exclusive maternal smoke exposure (SE) fails to reproduce most of the programming effects of maternal nicotine exposure, and in order to try to reproduce what really can happen to children from smoker parents who are exposed to cigarette components both by breast milk and by direct inhalation, we design this study where both dams and pups were exposed to tobacco smoke during lactation to better understand the immediate and late repercussions of early environmental smoking on rat offspring's development and endocrine function.…”
Section: Introductionmentioning
confidence: 99%